Diseño y simulación de un prototipo de máquina peladora de chontaduro para cooperativa Asochon de Villa Garzón (2021)
Currently the chontaduro is peeled manually, which implies low productions of raw material for the manufacture of by-products, with rates of 237.6 kg/day, which correspond to 20% compliance with the production plan, which is 1200 kg/day; therefore, to increase production, this research project proposes to design and simulate a prototype of a chontaduro peeling machine for the ASOCHON cooperative of Villa Garzón. The proposal allows a significant increase in the production of by-products such as: preserves, yogurt, flour, cakes, bread, yogurt, vacuum-packed, among others; mitigate the risks derived from the manual process, and the optimization of human resources to assign them to other control and support tasks. The methodology used for its development comprises 4 phases that start with the conceptualization, design, calculations and simulation of the abrasion drum and chassis by means of the Von Mises method; as a result of its application, a chontaduro peeling machine is obtained, composed of a cylindrical drum with an abrasive sheet with a capacity to process 30 Kg in 15 minutes, which means an average of 960 Kg/day, equivalent to an increase of 75% compared to the manual method. It is concluded that the design is reliable and satisfactory, since when applying the Von Mises method under maximum load conditions, there are no deformations, which allows it to perform its work adequately, as long as the rules of use and maintenance are complied with